Case report: Improved behavioral and psychiatric symptoms with repetitive transcranial magnetic stimulation at the bilateral DLPFC combined with cognitive and behavioral therapy in a patient with unilateral thalamic hemorrhage - Ahn, Hye Chan; Kim, Kyoung Tae (Frontiers in Neurology, 2022)
Behavioral and psychological symptoms are not uncommon after thalamic stroke, and are often intractable despite medication and behavioral interventions. Repetitive transcranial magnetic stimulation (rTMS) is as an adjunctive therapeutic tool for neuropsychiatric diseases, and bilateral rTMS has been recently introduced to maximize the therapeutic effect. Herein, we report the case details of a patient with unilateral left thalamic hemorrhage without cortical lesions who had treatment-resistant neuropsychiatric symptoms. We hypothesized that bilateral rTMS targeting the bilateral dorsolateral prefrontal cortices (DLPFCs) would positively affect thalamocortical neural connections and result in neuropsychiatric symptom improvement. The patient received a total of 10 sessions of bilateral rTMS over 2 weeks, applied at the DLPFCs, with high frequency in the left hemisphere and low frequency in the right hemisphere. After each rTMS treatment, computer-based cognitive-behavioral therapy was administered for 30 min. Behavioral and psychological symptoms, including hallucinations, aggressiveness, aberrant motor activity, disinhibition, and abrupt emotional changes, were significantly improved as assessed by the Neuropsychiatric Inventory Questionnaire. These effects persisted for up to 1 month. This case demonstrates the clinical potential of bilateral rTMS treatment in patients with intractable neurocognitive impairment after thalamic stroke.